Short-term impacts of embryonic thermal manipulation in mule duck, a kinetic study: new tools for metabolic programming - Andrieux, C.; Biasutti, S.; Zwick, LL; Marchand, M.; Panserat, S.; Houssier, M. (BMC genomics, 2025)
Background Temperature changes during embryogenesis, through a process called embryonic thermal programming, can modify the long-term thermotolerance of broilers or the hepatic metabolism of mule ducks. This study focused on the very short-term impacts on mule duck livers of such a programming which consist of increasing the incubation temperature by + 1°C, 16h/24h, from the 13th to 27th day of embryonic development. Using fluidigm technology, we analysed the impact of this temperature change on the relative expression of 81 genes involved in various metabolic pathways closely or remotely related to the fattening of the liver of mule ducks. Results Expression changes were first assessed during temperature increase (from 30 min to 7h, then 3 days, 7 days and 11 days after the start of modification), and at hatching (3 days after the end of temperature modification) in comparison with a group of animals not exposed to this programming. First, zootechnical measurements confirmed that the moderate discontinuous increase in embryonic temperature led to a drop in internal temperature and hatch weight, but did not reduce hatchability. Secondly, gene expression in all tested metabolic pathways was affected throughout the study, except for cell proliferation and epigenetic marks, which were only modulated during the thermal stimulus. The most strongly and durably modulated pathways, with significant changes in the expression of several genes at multiple sampling points, were lipid metabolism ( DGAT2, CEPT1, GPAT1, ACOX1 ), cellular stress ( HSPA5-HSP70 ), and thyroid hormone regulation ( NCOR ). Some genes such as SCD1 (lipid synthesis), DIO3 (thyroid hormone regulation), HSPA2 - HSP70, HSBP1, HSP90AA1 and IL18 (cellular stress) also showed modulation even after the thermal stimulus ended. Interestingly, the expression of genes involved in epigenetic and cell proliferation was only slightly affected by the temperature increase, except for ELP3 (epigenetic marks) which was significantly modulated at two points. Conclusion This study is the first to show the short-term impact of increased egg incubation temperature on gene expression in mule duck liver, from the start of the stimulus to hatching. These results could provide a valuable starting point for understanding the mechanisms of embryonic thermal programming that modulate hepatic metabolism in mule ducks.